The Cambridge Introduction to modernist poetry - Howarth, Peter 1973- (Cambridge Cambridge University Press, 2012)
"Modernist poems are some of the twentieth-century's major cultural achievements, but they are also hard work to read. This wide-ranging introduction takes readers through modernism's most famous poems and some of its forgotten highlights to show why modernists thought difficulty and disorientation essential for poetry in the modern world. In-depth chapters on Pound, Eliot, Yeats and the American modernists outline how formal experiments take on the new world of mass media, democracies, total war and changing religious belief. Chapters on the avant-gardes and later modernism examine how their styles shift as they try to re-make the community of readers. Howarth explains in a clear and enjoyable way how to approach the forms, politics and cultural strategies of modernist poetry in English"--Provided by publisher.
1. Why write like this? -- 2. Ezra Pound -- 3. T. S. Eliot -- 4. W. B. Yeats -- 5. Modernist America: Williams, Stevens, Moore -- 6. Avant-gardism: Mina Loy, Gertrude Stein, H. D. -- 7. Why is it so difficult? -- 8. Inside and outside modernism.
Includes bibliographical references (pages 223-246) and index.
Keywords: Poetry, Modern -- 20th century -- History and criticism; Modernism (Literature)